202k views
5 votes
Please help out anyone

Please help out anyone-example-1
User Bcarlso
by
5.3k points

1 Answer

5 votes

Answer:

The equation of the exponential function will be:

  • y = 12·(2)ˣ

Explanation:

The general exponential function is defined as

y = abˣ

Here,

a is the initial value and b is the growth factor

From the table, it is clear that the y-intercept is (0, 12). Note that the y-intercept can be determined by setting x=0 and solving for y.

here

at x=0, y=12

so a = 12

If we check the y-values, it is clear that every next value of y can be obtained by multiplying the previous y-value by 2.

In other words, the common multiplier = b = 2

Thus, the equation becomes

y = 12·(2)ˣ

Thus, the equation of the exponential function will be:

  • y = 12·(2)ˣ
User Curiousguy
by
4.7k points